On Measuring Aggregate "Social Efficiency" - Ravallion, Martin (World Bank, Washington, DC, 2014)
Cross-country comparisons of social indicators controlling for income and/or social spending have been widely used to measure and explain "social efficiency" analogously to "technical efficiency" in production. The author argues that these methods are clouded in ambiguities about what exactly is being measured. Standard methods of measuring technical efficiency require assumptions that seem unlikely to hold for social indicators. In the context of a simple parametric model of life expectancy, conditions are identified under which there will be a systematic pattern of bias in estimates of efficient health spending.